Kedudukan Anak Perempuan dalam Pembagian Harta Warisan Berdasarkan Hukum Waris Adat Timor Amanuban di Desa Fatuulan Kecamatan Ki’e Kabupaten Timor Tengah Selatan - Donna Yosepha Hektane Natonis; Orpa J. Nubatonis; Yossie M.Y. Jacob (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The purpose of this research is to analyze the position of daughters in the division of inheritance based on the customary inheritance law of Timor Amanuban in Fatuulan Village, Ki'e Subdistrict, South Central Timor District. The type of research used by the author is Empirical Legal research, the type of data used in this research is qualitative data. The data used in the research is based on the relevance of the source data, namely primary and secondary data. The results of this study suggest that the position of girls in the indigenous people of Timor Amanuban in Fatuulan Village who still apply the patrilineal system, who are entitled to get and receive inheritance rights are only sons, both biological children and adopted children from the father's side (semarga) who are legally valid. However, daughters are still considered and taken into account even though they are not visible as a form of respect and affection from people towards their children. The consideration of Timorese customary inheritance law Amanuban towards the position of girls who still adhere to the patrilineal system with no equality between girls and boys and indirectly shows an imbalance of rights. With the consideration of Timorese customary inheritance law, that girls are also taken into account to get their rights even though they are not the same and do not appear to be like boys giving their inheritance. This is because the gift is only seen as an appreciation and a sign of affection for the child.